Friends forever : a novel - Steel, Danielle (New York : Dell, 2012)
Forging inseparable bonds in childhood that reinforce them throughout their teen years, two girls and three boys go their separate ways as adults and encounter respective tragedies and transformations.
Originally published: New York : Delacorte Press, c2012.
Keywords: Female friendship -- Fiction; Boarding schools -- Fiction; Upper class -- Fiction; Bildungsromans; Fiction